Yoga for management of text neck Syndrome: Exploring the benefits of yoga in managing text neck Syndrome (Journal of Advances and Scholarly Researches in Allied Education, 2022)
“Text neck is a condition due to repetitive stress or overuse in the region of neck, induced by longterm use of smart phone or computer devices with bent the head downward and not moving for long time. Dueto frequent flexion of neck can change the curvature of cervical spine, supporting structures like ligaments,tendons, muscles, the bony parts, causing changes in body posture and induce pain on the neck andassociated areas. Yoga practice can bring back the head and spine into proper alignment by strengthens thesupporting structures like ligaments, muscles of neck and back.